Über eine Schar von geradlinigen Flächen zweiter Ordnung im dreidimensionalen elliptischen Raum - Ušpalienė, E. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Е. И. Ушпалене. Об одном семействе линейчатых квадрик в трехмерном эллиптическом пространствеE. Ušpalienė. Apie vieną antros eilės tiesialinijinių paviršių šeimą trimatėje elipsinėje erdvėje